Evaluation of Consortium Enzyme towards Kojic Acid Synthesis - S. Mat Radzi; K. M. W. Syamsul; Maryam Mohamed Rehan (Universiti Sains Islam Malaysia, 2024)
Consortium enzyme is a new approach in enzymatic esterification reaction to solve Kojic acid esters' low production. Combining a non-specific enzyme (Novozym 435) and a specific enzyme (Lipozyme RM IM) led to an improvement of enzymatic activity in the enzymatic routes. The findings proved that a significant percentage conversion of ester (29.2 %) was successfully achieved at the enzyme ratio (1:1) of Lipozyme RMIM and Novozym 435, the temperature at 50 ?C, amount of enzyme 0.12 g and 8 hours of reaction time. Moreover, the enzyme showed high stability against heat at 500C and can be used repeatedly up to the 5th cycle, as demonstrated by the high percentage conversion of kojic acid ester. This finding confirmed that consortium enzymes have significantly improved the reaction performance by promoting better catalytic efficiency due to the synergistic effect between combined enzymes.